Production Performance Analysis of Class II Hydrate-Bearing Layers Based on an Analytic Aquifer Model - Yu, Jing; Zhuo, Lubin; Chen, Yang; Sun, Wenchao; Liu, Yongge (Frontiers in Energy Research, 2021)
In the current numerical simulation studies, bottom water in Class II hydrate bearing layers is represented by grids with high water saturation which significantly extends the calculation time if the volume of the bottom water is large or grid size is small. Moreover, the influence of the bottom water volume on the depressurization performance of Class II hydrate-bearing layers has not been fully investigated. In this study, the Fetkovich analytic aquifer model was coupled with a simulation model of a hydrate reservoir to accelerate the simulation of Class II hydrate-bearing layers. Then the simulation results and calculation time were compared between the coupled model and the model in which the bottom water layer is only represented by grids. Finally, the influence of the bottom water volume on the productivity of gas and water in the depressurization method was investigated and the variation of pressure, temperature and hydrate saturation during the production process was analyzed. The results show that the coupled model can significantly reduce the simulation time of Class II hydrate bearing layer while ensuring calculation accuracy. When the pore volume of the aquifer increases to 20 times that of the bottom water layer, the computation time of single model in which bottom water layer is represented by grids is 18.7 times that of the coupled model. Bottom water invasion slows down the depressurization, and therefore, the larger the aquifer, the lower the peak value of gas production, and the later it appears. However, the invading bottom water can provide heat for hydrate dissociation; therefore, the gas production rate of the hydrate-bearing layer with bottom water is higher than that of the hydrate-bearing layer without bottom water in the late development stage. Generally, the presence of bottom water reduces the cumulative gas production and increases the cumulative water production; therefore, the larger the aquifer, the more unfavorable the depressurization development of the hydrate-bearing layer.